Social Determinants of Stunting in Indonesia - Efa Nugroho; Puput Arisma Wanti; Cahyani Wulan Suci; Bambang Budi Raharjo; Najib Najib (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Stunting is a form of malnutrition that causes growth disorders characterized by height that is not in accordance with age. Around 8.9 million Indonesian children experience suboptimal growth. This study aimed to determine the social factors associated with the incidence of stunting in Indonesia. The method used were secondary data processing from Indonesian family data collection in 2021. The population of this data collection were 66.207.139 families from 33 provinces in Indonesia. The research sample were 38.886.147 families. The variables analyzed were indicators of pre-prosperous families, environmental facilities, high risk pregnancy in couples of childbearing age, with the risk of stunting. Data were analyzed using linear regression. The results showed that the determinants of stunting are maternal education, parental occupation and income, environment, social and family support, and health service factors. Based on the analysis, there is a relationship between the social determinants of health according to healthy people and the increase in stunting cases in Indonesia.